2010
DOI: 10.4314/mejs.v2i2.57670
|View full text |Cite
|
Sign up to set email alerts
|

Integrated effect of seeding rate, herbicide dosage and application timing on durum wheat (<i>Triticum turgidum</i> l. var durum) yield, yield components and wild oat (avena fatua l.) control in south eastern Ethiopia

Abstract: Knowledge of optimal combinations of crop densities, herbicide dose and time of application could improve the effectiveness and net benefit of commonly used herbicides. A study was conducted at two locations in SARC on-station and farmer's field, South Eastern Ethiopia for two years from 2007 to 2008. The experimental design was randomized complete block (RCB) design with split-plot arrangement. Durum wheat (Triticum turgidum) seeding rates (recommended, 25% and 50% plus recommended rate) were arranged in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…The present study in agreement with the ndings, Haile [73] who reported that the lowest seeding rate (100 kg ha -1 ) resulted in harvest index of 3.851 tons ha -1 , which was signi cantly lower than harvest index obtained at the other seeding rates (150 and 175 kg ha -1 ). Likely, Burgos [85] and Abiot [52] reported that harvest index increased as seeding rate was increased from 50 to 100 kg ha-1 and from 100 to 150 kg ha -1 respectively.…”
Section: Weeding Intensitysupporting
confidence: 93%
See 1 more Smart Citation
“…The present study in agreement with the ndings, Haile [73] who reported that the lowest seeding rate (100 kg ha -1 ) resulted in harvest index of 3.851 tons ha -1 , which was signi cantly lower than harvest index obtained at the other seeding rates (150 and 175 kg ha -1 ). Likely, Burgos [85] and Abiot [52] reported that harvest index increased as seeding rate was increased from 50 to 100 kg ha-1 and from 100 to 150 kg ha -1 respectively.…”
Section: Weeding Intensitysupporting
confidence: 93%
“…The result shows that there are more effective tillers (6.06) at this location. Farmers' tactics included frequent two-time weeding (2W) but a smaller number of tillers (0.42).The ndings of Durem Wheat, as reported by Haile and Girma, [73] also con rmed.…”
Section: Effective Tiller Numbermentioning
confidence: 60%
“…In contrast, the lowest straw yield/fed was obtained from Eferst at the recommended rate alone in both seasons, respectively. Similar findings were reported by Pourazar and Baghestani (2010), Zhu et al (2010) and Haile and Girma (2010) who indicated that Topik herbicide gave high grain yield with the highest stability in wheat. However, Knezevic et al (2010) indicated that application of herbicides with adjuvants caused the increase of yield in comparison with plots treated with herbicide alone.…”
Section: Wheat Yield and Its Componentssupporting
confidence: 90%
“…Hence, enhanced interspecific competition in favour of wheat plants is negatively reflected in the total weight of weeds per unit area. These results are in line with the Bulut et al (2010) and Haile and Girma (2010) who suggested that crop density would be naturally less under low seeding rate, leaving many resources available for weeds and enabling them to establish quickly.…”
Section: Melilotus Indicus Fabaceaesupporting
confidence: 87%
“…As plants compete for available resources at high plant densities, extremely low plant densities may allow weed invasion. Wheat yield loss due to weed-infested fields was reduced using higher than recommended seeding rates (Haile, Girma, 2010). High plant density due to a high seeding rate results in greater intraspecific competition for moisture, sunlight, and essential nutrients (Iqbal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%